Implication of Other Legislations on Negotiable Instruments: A Study in the Light of Negotiable Instruments Act, 1881 - Sony KULSHRESTHA, Arun Dev PAREEK, Katha MATHUR, Mani Pratap SINGH, Khushboo SHARMA (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose of the Study: The study focuses on the applicability of other legislations on Negotiable Instruments, which are principally administered by the Negotiable Instruments Act, 1881. The objective is to make a well-established nexus among various provisions of civil, criminal and procedural laws, administering the Negotiable Instruments in India. Research Methodology: The research is conducted on the secondary data which includes the legislative enactments, a thorough study of the laws on NI and Evidence Law, Law of Contract and the Reserve Bank of India Act etc. Main Findings: It is found that the Principle Act which governs the NI in India is not exhaustive enough in itself. Moreover, in the matters of contradiction with other legislations, other laws supersede the Act of 1881. It gives a need of enacting a totally new enactment or to do major amendments to cover the gap or contradictions. The study reveals the deviation of principles in terms of interpretation of the provisions from the mother Acts. Implications of this study: The research is helpful to the enactment of the new/amended legislation on NI in India. It is also helpful to the researchers to understand the applicability and limitations of the present Act. Novelty/Originality of this Study: The research has covered the most untouched area of the NI, which creates the illusion of the implications of the provisions of the Act, when this is superseded by other legislations. An endeavor is made to make sense of the demand of a new enactment.